Struktur Nyanyian Togo dalam Upacara Adat Pati Karapau serta Implementasinya dalam Pembelajaran Seni Musik bagi Siswa SMA - Molo, Benediktus; Langgu, Paskalis R. (Paedagogie, 2026)
This study aims to (1) examine the musical structure of the Togo Chant as part of the sacred tradition of the Pati Karapau Customary Ceremony on Palu’e Island, and (2) develop a Togo Chant learning module as cultural arts teaching material for high school students to support the preservation of local culture. The research employs a qualitative descriptive approach and the Research and Development (R&D) method. The qualitative approach is applied to analyze the musical structure through song transcription, observation of musical functions, and studies of melody, rhythm, and composition. Meanwhile, the development of teaching materials follows the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was conducted through documentation, music transcription, and validation by subject matter and instructional design experts to assess the feasibility of the module. Data analysis involved descriptive techniques for musical structure and percentage analysis for module feasibility, as well as effectiveness testing through comparison of students’ pretest and posttest results. The findings indicate that the Togo Chant is diatonic music with a compositional structure consisting of an introduction, body, and conclusion, and serves ritualistic, entertainment, and religious functions. The developed learning module received a “good” category with an expert feasibility rating of approximately 80%. Furthermore, the module proved effective in improving student learning outcomes, as evidenced by an increase in average knowledge scores from 44.75 to 72.25 and skill scores from 50.5 to 80.5, with a significance level of < 0.05. The Togo Chant holds significant musical and cultural value that warrants preservation, and the developed learning module is deemed feasible and effective for use in high school cultural arts education. Integrating traditional music into formal education is a relevant strategy to strengthen cultural identity while enhancing students’ learning experiences.